Mabel and William Meed's cabin in Dawson, Y.T. ca. 1905. - Peck, Odbur C.
Left to right: William Meed, son Max, Mabel Meed (Mrs. William Meed), John Newton brother of Mabel. PH Coll 246.52 [Meed journal: "Our winter home in Dawson, 1905. My wife, our son Max and I stand together. Brother John on the right. Nigger [the dog] in snow. The structure in front provided a double entrance, necessary to prevent the escape of heat. The logs were placed with moss between them. The roof was of poles plus moss and a six-inch layer of earth."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number